2021
DOI: 10.1111/dom.14393
|View full text |Cite
|
Sign up to set email alerts
|

Preinfection glycaemic control and disease severity among patients with type 2 diabetes and COVID‐19: A retrospective, cohort study

Abstract: Type 2 diabetes (T2D) is one of the most common and important risk factors for severe health outcomes related to coronavirus disease-2019 (COVID-19). [1][2][3] Data from the French Coronavirus SARS-CoV-2 and Diabetes Outcomes (CORONADO) study in patients with COVID-19 infection showed that higher body mass index (BMI) and complications of diabetes were associated with disease severity and death, but they did not identify a link between glycaemic control and mortality. 4,5 However, other studies found an associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 20 publications
2
19
0
3
Order By: Relevance
“… 8 However, one study did indicate a significant positive association between single-point preinfection HbA1c, measured within 6 months, and the severity of COVID-19 illness. 33 In contrast to these previous investigations, our study considers a longer period glycemic control for an individual as an indicator for history of diabetes and severity (which are usually harder to evaluate) by using the 2 to 3-year longitudinal HbA1c. Here we successfully identified the 2 to 3-year longitudinal HbA1c to be a significant risk factor for COVID-19-related severity that can serve as a key clinical parameter related to management of COVID-19 for an individual patient and for assessing ICU use.…”
Section: Discussionmentioning
confidence: 99%
“… 8 However, one study did indicate a significant positive association between single-point preinfection HbA1c, measured within 6 months, and the severity of COVID-19 illness. 33 In contrast to these previous investigations, our study considers a longer period glycemic control for an individual as an indicator for history of diabetes and severity (which are usually harder to evaluate) by using the 2 to 3-year longitudinal HbA1c. Here we successfully identified the 2 to 3-year longitudinal HbA1c to be a significant risk factor for COVID-19-related severity that can serve as a key clinical parameter related to management of COVID-19 for an individual patient and for assessing ICU use.…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with those of previous studies. A retrospective cohort study of the association between pre‐infection glycemic control and disease severity in patients with type 2 diabetes and COVID‐19 in Israel found a gradual dose–response relationship between HbA1c level and the risk of severe COVID‐19 10 . A population‐based cohort study in England also suggested a higher risk of mortality from COVID‐19 in patients with either type 1 or type 2 diabetes with HbA1c levels >10.0% than in those with HbA1c levels of less than 6.5% 19 .…”
Section: Discussionmentioning
confidence: 99%
“…1 Several epidemiological studies have pointed to diabetes as one of the major co-morbidities significantly associated with poor outcomes in COVID-19 patients. [2][3][4] COVID-19 involves a cytokine storm mediated by overproduction of pro-inflammatory cytokines, which is related to disease severity. 1 Type 2 diabetes (T2D) may worsen the COVID-19 prognosis as it causes a state of chronic inflammation; in particular, it is associated with high levels of tumour necrosis factor α (TNFα), which contributes to insulin resistance, and low levels of the anti-inflammatory cytokine interleukin (IL)-10.…”
Section: Introductionmentioning
confidence: 99%
“…Coronavirus disease 2019 (COVID‐19) disproportionately affects patients with co‐morbidities 1 . Several epidemiological studies have pointed to diabetes as one of the major co‐morbidities significantly associated with poor outcomes in COVID‐19 patients 2‐4 …”
Section: Introductionmentioning
confidence: 99%